2016
DOI: 10.1080/10538720.2016.1155519
|View full text |Cite
|
Sign up to set email alerts
|

What does it mean to be a successful adult? Exploring perceptions of the transition into adulthood among LGBTQ emerging adults in a community-based service context

Abstract: This study qualitatively explores the application of emerging adulthood theory to lesbian, gay, bisexual, transgender, and queer (LGBTQ) emerging adults. Researchers explored perspectives of LGBTQ emerging adults and service organization staff on their experiences of aging out of youth services. Descriptions of what success looks like, and self-defined needs associated with the transition from youth to adulthood, were collected through interviews and focus groups. Four conceptual areas emerged from a thematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Emerging adulthood is a developmental stage between the ages of 18 and 25 years that is characterized by adaptations in social roles, identity, and social relationships (Arnett, 2016). For many sexual and gender minority (SGM) people (e.g., lesbian, gay, bisexual, transgender, queer, questioning, and other sexual and gender minority identities), emerging adulthood is characterized by exposure to new cisheteronormative social contexts and expectations (Tan et al, 2020; Wagaman et al, 2014). Due to the potential for fluidity and shift in gender identity, gender expression, and/or sexual orientation, SGM emerging adults frequently encounter concurrent gender and sexual minority stressors which may be covert (e.g., microaggressions) or overt (e.g., interpersonal victimization) in nature.…”
mentioning
confidence: 99%
“…Emerging adulthood is a developmental stage between the ages of 18 and 25 years that is characterized by adaptations in social roles, identity, and social relationships (Arnett, 2016). For many sexual and gender minority (SGM) people (e.g., lesbian, gay, bisexual, transgender, queer, questioning, and other sexual and gender minority identities), emerging adulthood is characterized by exposure to new cisheteronormative social contexts and expectations (Tan et al, 2020; Wagaman et al, 2014). Due to the potential for fluidity and shift in gender identity, gender expression, and/or sexual orientation, SGM emerging adults frequently encounter concurrent gender and sexual minority stressors which may be covert (e.g., microaggressions) or overt (e.g., interpersonal victimization) in nature.…”
mentioning
confidence: 99%
“…(2004) Baker, Durr, & Scott (2016) Mind Out (2016) O'Hara 2013 Paceley (2016) Painter, Scannapieco, Blau, Andre, and Kohn (2018) Pallotta Chiarolli and Martin (2009) The Proud Trust (2016) Powell, Ellasante, Korchmaros, Haverly, and Stevens (2016) Sadowski, Chow, and Scanlon (2009) Sansfacon et al. (2018) Steinke, Root-Bowman, Estabrook, Levine, and Kantor (2017) Wagaman, Keller, and Cavaliere (2016) Wilkerson et al. (2017) Wilkerson et al.…”
Section: Resultsmentioning
confidence: 99%
“…Parmenter et al (2020b) sought to understand identity development amongst young adults and found that, though participants were 20-25 years old therefore categorized as young adults in Erikson's intimacy versus isolation stage of development (Erikson, 1982), findings highlighted LGBTQ young adults' experiences of identity conflict and exploration. LGBTQ young adults expressed identity consolidation and conflicts in integrating their LGBTQ identity across their lives (Wagaman et al, 2016;Parmenter et al, 2020b). Particularly for LGBTQ young adults with intersecting ethnic or religious identities, their young adult experiences of identity integration were highly distressing and resulted in identity confusion (i.e., identity suppression, compartmentalization, and separation) and decreased levels of life satisfaction (Wagaman et al, 2016;Parmenter et al, 2020b).…”
Section: Erik Erikson's Stages Of Psychosocial Developmentmentioning
confidence: 99%
“…LGBTQ young adults expressed identity consolidation and conflicts in integrating their LGBTQ identity across their lives (Wagaman et al, 2016;Parmenter et al, 2020b). Particularly for LGBTQ young adults with intersecting ethnic or religious identities, their young adult experiences of identity integration were highly distressing and resulted in identity confusion (i.e., identity suppression, compartmentalization, and separation) and decreased levels of life satisfaction (Wagaman et al, 2016;Parmenter et al, 2020b). As Erikson's stages of psychosocial development has been understood as one of the classic stage theories of development, many researchers turn to Erikson's stages of psychosocial development, specifically Erikson's adolescent identity achievement versus conflict stage, to understand identity development in adolescents (Rageliene, 2016).…”
Section: Erik Erikson's Stages Of Psychosocial Developmentmentioning
confidence: 99%